Penguatan Praktik Community-Based Tourism sebagai Upaya Perbaikan Pengelolaan Desa Wisata Sidomulyo - Peni Arianita Wardani; Muhamad Farhan; Nur Afni Rachman; Achmad Fawwaz Nabiha; Taufikkurrohman Taufikkurrohman (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of tourist villages in Indonesia is increasing with government support and a shift in tourist interest towards educational and sustainable tourism. Sidomulyo Tourism Village, one of the tourist destinations in Jember Regency, has shown the potential for developing community-based tourism (CBT). However, the management of this village is still under the auspices of the village government, which could lead to continued dependency in the future. Community involvement is still limited because the village government decides the entire planning and management process. Through educational training, this community service program aims to strengthen CBT practices in the Sidomulyo Tourism Village. The process of transferring knowledge and experience is carried out by a manager of one of the independent tourist villages in Indonesia. This activity includes training and evaluation sessions. The results show increased participants' understanding of CBT and independent management of tourist villages. This program recommends developing priority attractions and improving digital marketing as initial steps to support sustainable tourism in the village.